Learning interactions with and about robotic models - Verner, Igor M.; Cuperman, Dan (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
This paper considers learning interactions, in which the student inquires into a biological system and develops its representation in the form of a robotic model using the PicoCricket robot construction kit. Our study follows-up the learning interactions and students' perceptions of the modeling experience.